Hole Conductor Free Perovskite-based Solar Cells - Etgar, Lioz.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book discusses the promising area of perovskite-based solar cells. It places particular emphasis on a highly unique perovskite solar cell structure, focusing on the special properties of hybrid organic-inorganic perovskites. As such, it offers readers sound essentials, serving as building blocks for the future development of this rapidly evolving field.
Keywords: Optical materials; Renewable energy sources; Condensed matter; Microtechnology; Microelectromechanical systems; Optical Materials; Renewable Energy; Condensed Matter Physics; Microsystems and MEMS